Changes seen in the body of an elderly patient suffering from diabetes - Klaudia Kwiatkowska; Mariusz Wąsicki; Mateusz Modrzejewski; Mateusz Porada; Dorota Szewczak; Ewa Rozmarynowicz; Marta Madziarska; Aneta Karło; Marlena Kontowicz; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Background: Diabetes is a foreign disease today. This is a chronic, metabolic disease that is characterized by elevated blood glucose levels. There are many types of disease. Each of them has different characteristics. The key in the fight against the disease is to perform appropriate laboratory tests to diagnose diabetes and to introduce appropriate treatment to prevent many complications, e.g. impairment of: vision, kidneys, cardiovascular system or hearing. Material and methods: A proper review of the literature was used, which identifies risk factors, complications and proper management in diagnosing diabetes. Results: The growing problem of diabetes forces us to find the most accurate way to treat the disease. Performing reliable diagnostics is crucial. The reference method (IDMS) and methods used in routine diagnostics, oxidase hexokinase are the basic and necessary laboratory tests used in the diagnosis of diabetes. Conclusions: In the coming years, the number of patients suffering from diabetes will continue to grow. Diagnosis and treatment of this disease is extremely important, because neglecting the disease can have many serious consequences for healthy physical and mental functioning. The basis is the performance of correct tests, which allows for proper treatment.